Extraordinary Areal and Volumetric Performance of Flexible Solid‐State Micro‐Supercapacitors Based on Highly Conductive Freestanding Ti3C2Tx Films. (27th June 2018) - Huang, Haichao; Su, Hai; Zhang, Haitao; Xu, Ludi; Chu, Xiang; Hu, Chunfeng; Liu, Huan; Chen, Ningjun; Liu, Fangyan; Deng, Wen; Gu, Bingni; Zhang, Hepeng; et al.
Abstract: Approaching state‐of‐the‐art areal and volumetric capacitances while maintaining high‐power characteristic is a big challenge that promotes practical application of flexible solid‐state micro‐supercapacitors (MSCs), which have recently attracted great attention with the rapid development of flexible microelectronics. Herein, it is reported that freestanding extrahigh conductive Ti3 C2 T x (MXene) films with excellent flexibility and effectively controlled thickness ranging from 1–21 µm performed as excellently scalable and flexible solid‐state MSCs owing to their ultrahigh underlying electrical conductivity (up to 1.25 × 10 5 S m −1 ) and self‐functionalized surfaces (O, OH, and F terminations). Amazingly, freestanding conductive Ti3 C2 T x based flexible solid‐state MSCs with interdigital electrodes and polyvinyl alcohol/sulfuric acid (PVA/H2 SO4 ) gel electrolyte display outstanding areal capacitances of 340 mF cm −2 at 0.25 mA cm −2 based on the two working electrodes. Moreover, the maximum corresponding volumetric capacitance and energy density of flexible solid‐state MSCs reach up to 183 F cm −3 and 12.4 mWh cm −3, which is on the topmost level among all the unconventional supercapacitors to date. Compared with materials currently used in MSCs, this freestanding conductive Ti3 C2 T x shows potential and scalability in increasing overall micro‐supercapacitor performance, which evidently sheds light on promising application of freestanding conductive MXenes for next‐generation flexible, portable, and integrated MSCs. Abstract : The freestanding highly conductive Ti3 C2 T x films with effectively controlled thickness ranging widely from 1 to 21 µm and good flexibility are prepared via vacuum filtration. Flexible solid‐state micro‐supercapacitors based on freestanding Ti3 C2 T x films exhibit high areal capacitance up to 340 mF cm −2 and ultrahigh volumetric capacitance of 183 F cm −3 and corresponding energy density of 13 mWh cm −3 .